If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 16 = 6x + 1 Reorder the terms: 16 + 5x = 6x + 1 Reorder the terms: 16 + 5x = 1 + 6x Solving 16 + 5x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 5x + -6x = 1 + 6x + -6x Combine like terms: 5x + -6x = -1x 16 + -1x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -1x = 1 + 0 16 + -1x = 1 Add '-16' to each side of the equation. 16 + -16 + -1x = 1 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 1 + -16 -1x = 1 + -16 Combine like terms: 1 + -16 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15
| 2(1)+y=-4 | | -(3a+6b)-(a-11b)= | | 5+2x-3x^2=0 | | x^2-13x-21=-7x-5 | | 10*5+66-56-12-510=x | | 148-5x=31x+20 | | 5a+6=4 | | 5x^2+10x-25= | | 37x(3*1.5)=4150 | | 4-5x=1.5 | | 3xy=4x-1 | | 12y+x=180 | | 2(2x-4)=12x | | 8-2x=x-2 | | x^2-14x+25=-3x-3 | | 0.4x+0.2=1 | | r-6=13 | | 15x-5=12x-8 | | -4y-4=-3y-8 | | 3=x^2-8x+15 | | x^3=3.9e-11 | | b-10=-16 | | 162-2x=43x+22 | | 9-p^2+8p-16=0 | | -38-4x=-6(1+6x) | | 9=3x+11 | | -5x+6=2x-8(4x-7) | | 5c^2+45c=0 | | 6+7w=10 | | 5c^2+45=0 | | 8w-5=0 | | 4w+7=100 |